Teaching biology in basic education: production of teaching models and use of ludic practices (Research, Society and Development, 2021)
One of the great challenges for biology teachers is still the lack of teaching materials that can facilitate and improve students' understanding of the content taught. Therefore, the objective of this work was to present the process of building didactic models with low-cost materials for use in innovative methodological practices in teaching biology in basic education through playfulness. In this exploratory and descriptive research with a qualitative and quantitative nature, we use low-cost materials, in addition to reusable objects to produce biological models and develop practical recreational activities. With the development of the work, it was possible to make two didactic biological models: a plasma membrane model and another for an animal cell. A comic book was produced for the study of transgenics, in addition to the development of three practical activities using reusable materials (practice on the ABO blood system, practice on Mendel's first law and practice on cell division). It was possible to verify that the activities carried out in the classes favored the teaching and learning process, making learning more meaningful, relaxed and dynamic. We also point out that the teacher needs to have clear and concise objectives about the content to be taught, so that he can explore and apply practical activities through playfulness.